Plant and arthropod species composition of sown and semi-natural pasture communities of three Azorean islands (Santa Maria, Terceira and Pico) - Borges, Paulo A. V. (1999)
Recent sowed and old semi-natural pastures from three Azorean islands (Santa Maria, Terceira and Pico) were investigated in terms of plant and arthropod species composition. Semi-natural sites were shown to be well suited to reveal distinct within island trends in semi-natural pasture communities. Variation in the composition of the vascular plants follows an altitudinal gradient, which is, a dry-wet gradient, and also human influences. It is in Santa Maria, as well as in the recent sown pastures of Terceira, that the influence of human activities on vascular plant communities is most dramatic. However, for arthropods these factors seem to be less important. Variation in the species composition of arthropod assemblages within each island is less evident, and the composition of sites reflects more regional (biogeographic) factors. The results also emphasize the importance of non intensive pasture management practices in the Azores for the colonization of this habitat by endemic arthropod species. Both the vascular plant and arthropod data, subject to analysis using Sörensen’s Index of Similarity reveal that, with minor exceptions, there is a clear separation of habitats only within islands. Moreover, similar overall patterns are obtained using TWINSPAN, reinforcing the importance of regional processes in shaping the arthropod composition of the Azorean pastures.